Analisis Kandungan Zat Gizi dan Uji Organoleptik Keripik Daun Torbangun (Coleus amboinicus Lour) - Anita Sembiring (Kupang Journal of Food and Nutrition Research, 2020)
This study aims to determine the nutritional value and organoleptic test of Torbangun leaf chips. The results of this study are expected to provide information and an overview of the benefits of local food as functional food to assist in increasing the scope of exclusive breastfeeding and improving the health status of the community, especially women. This type of research is an experimental study that is to know the nutritional content and acceptability of Torbangun leaf chips. This research was conducted in June 2019 until October 2019. The process of making chips is carried out in the Food Processing Laboratory Nutrition Study Program of the Health Ministry of Health Kupang Kupang. Organoleptic test was conducted at the Laboratory of Organoleptic Nutrition Study Program of the Poltekkes Health Ministry of Health Kupang. Analysis of the chemical properties of the product (proximate) was carried out at the Animal Husbandry Laboratory and Bio Science Laboratory of Nusa Cendana University, Kupang. From the results of the organoleptic test conducted by 35 panelists stated that the panelists liked the taste, texture, color and aroma of the fried and baked Torbangun chips. This is shown from the value of organoleptic test results ranging from 1 to 2, namely between likes and likes. However panelists are more likely to like fried chips than in the oven. This is indicated by the results of the Mann Whitney test which states there are significant differences in taste between fried chips and those in the oven. Likewise the aroma of chips, significantly different. Panelists prefer the aroma of fried chips to those in the oven. The content of protein and fiber content in Torbangun chips are fried and in the oven there is no difference. The fat content in fried Torbangun chips is higher than in the oven. Inversely proportional to the carbohydrates in Torbangun chips in the oven are higher than those fried. Calcium levels in the Torbangun chips in the oven are much lower than those in the fry. The iron content in the Torbangun chips in the oven is also lower than those in the fry.